Comparison of strategies to reduce meticillin-resistant Staphylococcus aureus rates in surgical patients: a controlled multicentre intervention trial. Issue 9 (19th September 2013) - Lee, Andie S; Cooper, Ben S; Malhotra-Kumar, Surbhi; Chalfine, Annie; Daikos, George L; Fankhauser, Carolina; Carevic, Biljana; Lemmen, Sebastian; Martínez, José Antonio; Masuet-Aumatell, Cristina; Pan, Angelo; Phillips, Gabby; et al.
Abstract : Objective: To compare the effect of two strategies (enhanced hand hygiene vs meticillin-resistant Staphylococcus aureus (MRSA) screening and decolonisation) alone and in combination on MRSA rates in surgical wards. Design: Prospective, controlled, interventional cohort study, with 6-month baseline, 12-month intervention and 6-month washout phases. Setting: 33 surgical wards of 10 hospitals in nine countries in Europe and Israel. Participants: All patients admitted to the enrolled wards for more than 24 h. Interventions: The two strategies compared were (1) enhanced hand hygiene promotion and (2) universal MRSA screening with contact precautions and decolonisation (intranasal mupirocin and chlorhexidine bathing) of MRSA carriers. Four hospitals were assigned to each intervention and two hospitals combined both strategies, using targeted MRSA screening. Outcome measures: Monthly rates of MRSA clinical cultures per 100 susceptible patients (primary outcome) and MRSA infections per 100 admissions (secondary outcome). Planned subgroup analysis for clean surgery wards was performed. Results: After adjusting for clustering and potential confounders, neither strategy when used alone was associated with significant changes in MRSA rates. Combining both strategies was associated with a reduction in the rate of MRSA clinical cultures of 12% per month (adjusted incidence rate ratios (aIRR) 0.88, 95% CI 0.79 to 0.98). In clean surgery wards, strategy 2 (MRSA screening, contact precautions and decolonisation) was associated with decreasing rates of MRSA clinical cultures (15% monthly decrease, aIRR 0.85, 95% CI 0.74 to 0.97) and MRSA infections (17% monthly decrease, aIRR 0.83, 95% CI 0.69 to 0.99). Conclusions: In surgical wards with relatively low MRSA prevalence, a combination of enhanced standard and MRSA-specific infection control approaches was required to reduce MRSA rates. Implementation of single interventions was not effective, except in clean surgery wards where MRSA screening coupled with contact precautions and decolonisation was associated with significant reductions in MRSA clinical culture and infection rates. Trial registration: clinicaltrials.gov identifier: NCT00685867